The role of the family physician in the fight against Coronavirus disease 2019 in Nigeria - Tijani I.A. Oseni; Ramatu O. Agbede; Bolatito B. Fatusin; Michael A. Odewale (AOSIS, 2020)
The Coronavirus disease 2019 (COVID-19) pandemic has been ravaging Nigeria and the world with increasing morbidity and mortality. Despite efforts by the Nigerian government implemented through the Nigerian Centre for Disease Control (NCDC) to reduce the scourge of the disease through public enlightenment and regular updates, the number of new cases and mortalities from COVID-19 are still increasing. Family physicians (FPs) who are the first contact of care for most patients accessing private and public health facilities in Nigeria have been working tirelessly to reduce the scourge of the pandemic in Nigeria. They continuously update themselves through regular webinars and online resources and guidelines provided by the Society of Family Physicians of Nigeria (SOFPON). Measures adopted by FPs across the country in the fight against the scourge include triaging patients as they present to the family medicine clinics; health education and enlightenment of the populace; and ensuring social distancing, regular handwashing and compulsory use of face mask by both physicians and patients during clinical consultations. Other measures include incorporating family-focused behavioural interventions in their practice, home-based care to reduce the number of persons visiting the hospital, telemedicine and Hospice and palliative care services to the elderly and terminally ill. In conclusion, FPs in Nigeria are helping to reduce the scourge of COVID-19 through patient education and innovative healthcare delivery that does not put patients at increased risk of the disease whilst promptly recognising potential COVID-19 patients and referring them for early diagnosis and treatment.